Maximizing performance of apparel manufacturing industry through CAD adoption. (18th December 2020) - Chaudhary, Sarita; Kumar, Pardeep; Johri, Prashant
Textile and apparel manufacturing industry of India is second highest employment generator sector and largest contributor to India's GDP. Unfortunately, it lacks behind in innovations and adoption of technology to meet the challenges. The basic problem remains as how to bring varied designs to market quickly with less efforts and cost. The adoption of CAD technology offering enormous benefits to apparel manufacturers in India. It makes quick and efficient revisions in apparel design changes including colour adjustments on fabric pattern and resizing garments. CAD system enable designers to produce more accurate designs with less chance of mistakes by saving cost and time. Its integration with CAM offers many advantages during manufacturing process and makes the apparel production faster with consistent and accurate results every time. As all information related to design and production are stored in file format, it makes very easy to produce the same design again without repetition of previous activities. The introduction of CAD technology in the industry resulted to improved efficiency of the design process due to automation of routine design tasks, increased employee productivity and shortened lead time in the product development process. This study highlights on adoption of CAD technology, limitations and its impact on business.